Dietary intake, levels of trace elements and intelligence quotient (IQ) among huffaz students from selected tahfiz schools in Selangor - Farah Wahida Ibrahim,; Santibuana Abd Rahman,; Nor Malia Abd Warif,; Ahmad Rohi Ghazali,; Faisal Ariffin,; Ismarulyusda Ishak,; Nur Farahin Abdul Rahman,; Dzalani Harun,; Hanis Mastura Yahya,; Sabri Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Tahfiz education has been well accepted by Muslims in Malaysia. Memorizing the Quran through rote learning can assist in improving the brain ability to process, store information and build memory. In addition, dietary intakes were reported to contribute in the process of memorizing the Quran and to increase the levels of intelligence (IQ) among huffaz students. This cross-sectional study was conducted to measure and to determine the correlation between IQ and dietary intake as well as between IQ and the level of trace elements among students in selected tahfiz schools and non-tahfiz school in Selangor. Questionnaires were used to obtain demographic data. Dietary intake was assessed via 3 days dietary record. Levels of trace elements in the nail samples were analyzed by using ICP-MS. Test for intelligence using WASI-II was conducted to measure the students’ IQ. The results showed that there was a moderate positive correlation between IQ and carbohydrate (r = 0.425, p < 0.001, a weak positive correlation between IQ and energy (r = 0.260, p < 0.05), vitamin B6 (r = 0.189, p < 0.05), vitamin B12 (r = 0.207, p < 0.05) and vitamin C (r = 0.211, p < 0.05). The levels of trace elements in nail samples showed no correlation with IQ, whereas there were moderate positive correlations between IQ and dietary zinc (r = 0.375, p < 0.001) as well as between IQ and dietary iron (r = 0.303, p < 0.001). There was also a moderate positive correlation between IQ and the level of memorization (r = 0.375, p < 0.001). The results of stepwise multiple linear regression showed that al-Quran memorization influence the level of IQ by 20 %. As a conclusion, dietary intake of certain nutrients including energy, vitamins and selected trace elements can potentially improve memorization activities and also IQ.